Avaliação e comparação do número de cetano obtido por métodos alternativos (normatizados e não normatizados) uma análise estatística. - Lima, Anderson Eduardo Alcântara de (2012)
In Brazil, the major employability of diesel oil is in the road system of cargo transport which is necessary for a rigorous accompaniment of the ignition quality of this fuel. Among the physical and chemical properties, Cetane Number (CN) is one of the most common indicators of the diesel quality. Beyond the standard method (ASTM D613) for CN determination, there are others alternative methods, such as ASTM D6890, ASTM D4737, through infrared spectroscopy and the portable IROX DIESEL. This work aimed to evaluate and compare alternative methods for CN determination and applying non-parametric statistical tests (Friedman, Wilcoxon). There were selected randomly 80 samples that were in accordance with ANP specifications and subsequently assayed in triplicate. According to statistical analysis, the CN determinations through ASTM D6890 and infrared spectroscopy have no significant differences at a significance level of 5%. CN results through ASTM D4737 and IROX DIESEL were statistically different from each other and when they are compared with the previous mentioned methods at a significance level of 5%. The infrared spectroscopic technique shows to be an alternative for obtaining CN if it is included in diesel oil specifications because it is a technique that requires less cost of implementation and maintenance, fast and accurate determination requiring no external calibration and easy operability.